Parental Experience of the Children with Gastrointestinal Stoma in Kanti Children Hospital, a Tertiary Level Children Hospital in Nepal - Manandhar, Smriti; Shrestha, Sarala; Shrestha, Sangita; Maharjan, Mankeshari (Journal of Karnali Academy of Health Sciences, 2023)
Background: The gastrointestinal stomas are seen as the obligatory condition for the treatment of children with gastrointestinal malfunction where their parents have to face various challenges. The lived experience of parents having children with gastrointestinal stomas was explored in this study. Methods: Qualitative phenomenological research design was used. Data were gathered by interviewing total 11 mothers with children having stoma for at least 2 weeks and admitted in a hospital. Thematic analysis was done with obtained data. Results : Six major emergent themes from the study were the parent’s journey with child’s health, challenges faced, resilience in caring the child, change in family life, support system and socio-cultural perception and influence. Conclusion: Parents of the children with the stoma face a range of problems and challenges. So, to sustain a betterand conducive life of the parent and their children with stoma, parental resilience must be enhanced by developing an integrated support in the journey of the parenthood.